Pengaruh Metode Al-Barqy Terhadap Kemampuan Membaca Al-Qur’an di MDA Nurul Ihsan Mudiak Lolo Barat Kecamatan Sungai Pagu Kabupaten Solok Selatan - Nurul Irvani; Junaidi Junaidi; Albaihaqi Anas; Nurhasnah Nurhasnah (Jurnal Budi Pekerti Agama Islam, 2024)
The purpose of this study was to determine how the Al-Barqy method affects the ability to read the Al-Qur’an at MDA Nurul Ihsan Mudiak Lolo Barat Sungai Pagu District South Solok Regency. This research uses pre-experimental methodology and is quantitative in nature. The number of grade I-IV MDA students who became the population of this study were 42 students. Collecting odd semester grades, then doing a normality test, the researcher determines a random sample as a sampling technique. Tests were used to collect data. Analysis of data using descriptive analysis and t-test. The results of the study based on the results of the Paired Sample T-test test obtained a t score of 9.376> t table which is 1306, and the probability value of sig. (2-tailed) 0.000 <0.05 so that it can be inferred that Ha is accepted and Ho is rejected which shows that there is a significant effect of the Al-Barqy method on the ability to read the Qur’an to students at MDA Nurul Ihsan Mudiak Lolo Barat, Sungai Pagu District, South Solok Regency.